Identification of a functional polymorphism within the 3′-untranslated region of denticleless E3 ubiquitin protein ligase homolog associated with survival in acral melanoma. (September 2019) - Yang, Lu; Dai, Jie; Ma, Meng; Mao, Lili; Si, Lu; Cui, Chuanliang; Sheng, Xinan; Chi, Zhihong; Yu, Sifan; Xu, Tianxiao; Yu, Jinyu; Kong, Yan; et al.
Abstract: Background: High expression of denticleless E3 ubiquitin protein ligase homologue (DTL) correlates with poor disease-free survival and overall survival in cutaneous melanoma, but the molecular features and clinical significance of this gene in acral melanoma (AM) remain unclear. Methods: The expression levels of DTL were compared between AM and benign melanocytic nevi using existing Gene Expression Omnibus data and validated in fresh frozen tissues. Two candidate tag single-nucleotide polymorphisms (SNPs) in the 3′-untranslated region (3′UTR) of DTL in patients with AM were sequenced and analysed for their association with survival in a discovery cohort (n = 570), and the significant SNP was subjected to a replication cohort (n = 201). The expression of DTL was evaluated by immunohistochemistry. The microRNA interacting with rs11275300:C > G was predicted using in silico target prediction tools and validated by in vitro analysis. Results: DTL was overexpressed in AM compared with benign melanocytic nevi. rs11275300:C > G was found to be significantly associated with progression-free survival and overall survival of patients with AM in both cohorts and the combined cohort. Furthermore, the DTL expression level in the patients with the rs11275300:G allele was higher than that in patients with the CC genotype. In vitro analysis demonstrated that DTL was a direct target of hsa-miR-4672, and the rs11275300:G allele interfered with the binding affinity of hsa-miR-4672 with the 3′UTR of DTL and thereby increased DTL expression. Conclusion: The rs11275300:G allele in the 3′UTR of DTL may lead to a poor prognosis and allele-specific increase in the expression of DTL by post-transcriptional regulation in AM. Highlights: The genetic variant rs11275300:C > G )is associated with progression-free survival and overall survival in acral melanoma. The rs11275300:C > G genotype correlates with DTL mRNA and protein expression. The G allele of rs11275300 of hsa-miR-4672 with the 3′UTR of DTL and affects post-transcriptional regulation.